Regulating the size and spatial distribution of Pd nanoparticles supported by the defect engineered metal–organic framework HKUST-1 and applied in the aerobic oxidation of cinnamyl alcohol. Issue 14 (21st June 2019) - Guo, Penghu; Fu, Qi; Yildiz, Ceylan; Chen, Yen-Ting; Ollegott, Kevin; Froese, Christian; Kleist, Wolfgang; Fischer, Roland A.; Wang, Yuemin; Muhler, Martin; Peng, Baoxiang
Abstract : A series of novel Pd@DE-HKUST-1(Cu/Pd) catalysts with different pydc feeding ratios were successfully synthesized. The size regime and the spatial distribution of the Pd NPs can be controlled by the amount of framework incorporated pydc. Abstract : The functional composite of metal nanoparticles (NPs) and defect-engineered metal–organic frameworks (DE-MOFs), NPs@DE-MOFs, is an emerging field of MOF materials chemistry. Herein, we report on a series of novel Pd-NPs@DE-HKUST-1(Cu/Pd) catalysts containing both micro- and mesopores through the incorporation of the defect-generating linker 2, 6-pyridyldicarboxylate (pydc). The Pd NPs are formed by partial reduction of the Pd 2+ sites of the pristine mixed-metal DE-HKUST-1(Cu/Pd) with methanol. The size regime and the spatial distribution of the Pd NPs can be controlled by the amount of framework-incorporated pydc. The samples exhibit superior catalytic activity in the aerobic oxidation of cinnamyl alcohol as compared to the parent HKUST-1.